Urgensi Disiplin Kerja dan Motivasi dalam Upaya Peningkatan Efektifitas Kerja Pegawai - Niken Wulandari; Hernawaty Hernawaty; Sela Selvia (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study explores the impact of the work effectiveness of service employees influenced by work discipline and motivation. This study uses a quantitative approach with a survey method. The number of samples for this scientific study is 53 employees. The data collection technique used is a questionnaire. SPSS Version 27 software is used to process the data, involving classical assumption tests as well as multiple linear regression. The results of scientific studies show that employee work effectiveness has a positive and significant impact on work discipline and motivation together. Individually, these two factors have also been proven to have a positive and significant effect. work discipline and work motivation have a very strong relationship with employee work effectiveness, with an R2 value of 0.603. This means that 60.3% of Employee Work Effectiveness can be described by these two variables